Is statin-modified reduction in lipids the most important preventive therapy for cardiovascular disease? A pro/con debate - Richard Hobbs; Maciej Banach; Dimitri P. Mikhailidis; Aseem Malhotra; Simon Capewell (2016)
The most prescribed medications in the world are statins, lipid modifiers that have been available for over 25 years and amongst the most investigated of all drug classes. With over a million patient years of trial data and publications in the most prestigious medical journals, it is remarkable that quite so much debate remains as to their place in healthcare. They have had a bittersweet passage, with vocal concerns over their possible risks, from suicide to cancer, and allegations that they do not work in women or the elderly, to statements that the whole published dataset, on over 200,000 patients consenting to enter trials, was fatally compromised by being industry-funded by and large. On the other side, there have been billions of dollars spent on generating their evidence base followed by promotion which has returned that investment many times over in profits, and a powerful scientific lobby that argue they are wonder drugs and that continued nihilism on their value risks patient lives. So who is right?